Leószilárdite, the first Na, Mg-containing uranyl carbonate from the Markey Mine, San Juan County, Utah, USA. (1st October 2017) - Olds, Travis; Sadergaski, Luke; Plášil, Jakub; Kampf, Anthony; Burns, Peter; Steele, Ian; Marty, Joe; Carlson, Shawn; Mills, Owen
Leószilárdite (IMA2015-128), Na6Mg(UO2)2(CO3)6·6H2O, was found in the Markey Mine, Red Canyon, White Canyon District, San Juan County, Utah, USA, in areas with abundant andersonite, natrozippeite, gypsum, anhydrite, and probable hydromagnesite along with other secondary uranium minerals bayleyite, čejkaite and johannite. The new mineral occurs as aggregates of pale yellow bladed crystals flattened on {001} and elongated along [010], individually reaching up to 0.2 mm long. More commonly it occurs as pale yellow pearlescent masses to 2 mm consisting of very small plates. Leószilárdite fluoresces green under both longwave and shortwave ultraviolet light, and is translucent with a white streak, hardness of 2 (Mohs), and brittle tenacity with uneven fracture. The new mineral is readily soluble in room temperature H2O. Crystals have perfect cleavage along {001}, and exhibit the forms {110}, {001}, {100}, {101} and {101}. Optically, leószilárdite is biaxial (–), α = 1.504(1), β = 1.597(1), γ = 1.628(1) (white light); 2V (meas.) = 57(1)°, 2V (calc.) = 57.1°; dispersion r > v, slight. Pleochroism: X = colourless, Y and Z = light yellow; X < Y ≈ Z. The average of six wavelength dispersive spectroscopic analyses provided Na2O 14.54, MgO 3.05, UO3 47.95, CO2 22.13, H2O 9.51, total 97.18 wt.%. The empirical formula is Na5.60Mg0.90U2O28C6H12.60, based on 28 O apfu. Leószilárdite is monoclinic, C2/m, a = 11.6093(21), b = 6.7843(13), c = 15.1058(28) Å, β = 91.378(3)°, V = 1189.4(4) Å3 and Z = 2. The crystal structure (R1 = 0.0387 for 1394 reflections with Iobs > 4σI), consists of uranyl tricarbonate anion clusters [(UO2)(CO3)3]4– held together in part by irregular chains of NaO5(H2O) polyhedra sub parallel to [010]. Individual uranyl tricarbonate clusters are also linked together by three-octahedron units consisting of two Na-centred octahedra that share the opposite faces of a Mg-centred octahedron at the centre (Na–Mg–Na), and have the composition Na2MgO12(H2O)4. The name of the new mineral honours the Hungarian-American physicist, inventor and biologist Dr. Leó Szilárd (1898–1964).